Modernization of the brake system of unwinding on rope machines - S. S. Konovalchuk; I. M. Livshits (Литьë и металлургия, 2021)
In order to reduce the cost of producing metal cord in the hardware shops of OJSC “BSW” – the Management Company of the Holding “BMC”, work is underway to modernize and select materials for replaceable technological equipment. In the process of twisting the metal cord on the unwinding of the power coils of rope machines, brake devices are used, consisting of a disk and sectors (pads) fixed in a chain. The elements of the unwinding unit are in constant contact, providing the necessary tension force for unwinding a thin wire. The performance of the braking devices affects the manufacturability of the twist, the absence of breaks, the density and geometric arrangement of the wires in the twisted metal cord that meets the requirements of consumers.Due to constant contact friction at high linear speeds, the brake pads wear out, which leads to emergency operation of the equipment. The article considers the test results of the modified thin wire unwinding unit and the impact of modernization on the service life of brake pads.